The Role of RIPK1/3 in Adult Onset Still’s Disease Patients With Liver Damage: A Preliminary Study - Liu, Xuesong; Guo, Ruru; Meng, Xinyu; Fang, Jianchen; Lu, Liangjing (Frontiers in Immunology, 2020)
Objective: This study aimed to investigate the role of lymphocyte distribution in adult onset still’s disease (AOSD) with liver dysfunction, and further prospectively explore whether receptor interacting serine/threonine kinases (RIPKs) play a role in the pathogenesis of AOSD especially the liver involvement. Methods: Seventy-two AOSD patients and 19 cases of healthy control were retrospectively reviewed, the AOSD group was divided into liver damage (LD) group and non-liver damage (NLD) group, the distributions of lymphocytes in peripheral blood were analyzed. Another independent 19 AOSD patients and 20 healthy controls were recruited for prospective study of RIPKs; the RIPKs in peripheral blood lymphocytes were detected by flow cytometry. Liver biopsy specimens were obtained from one AOSD patient and underwent immunochemistry analysis with RIPK1 and RIPK3 antibody. Results: In retrospective study, AOSD showed significantly abnormal lymphocyte distribution and disease activity were positively correlated with percentage of CD3+ T cell. LD patients had higher frequencies of CD3+ T cell especially higher CD8+ T cell (all p< 0.05). In the prospective study, RIPKs in lymphocytes were significantly higher in AOSD patients than that of HC, and were positively correlated with ESR and disease activity (all p<0.05). Among AOSD patients, LD group showed a higher RIPKs expression. ROC curve analysis indicated that RIPKs could be potential biomarker in the diagnosis of AOSD. Conclusions: Abnormal lymphocytes distribution and RIPKs expression were detected in AOSD. Aberrant expression of RIPKs in lymphocytes might be involved in the pathogenesis of AOSD. RIPKs could be candidate marker for AOSD.